Zeus : king of the gods - O'Connor, George (Olympians, 2010)
Terrified of being killed by one of his children, Kronos devours each of his offspring in turn. Only Zeus, the youngest, is saved. Though raised to enjoy a life of leisure, Zeus must fulfill his destiny and lead a new race of gods--and he must begin by destroying his own father.